Associated factors study into the belated screening for leprosy in Benin. - Ronald Sètondji Gnimavo; Ghislain Emmanuel Sopoh; Parfait Djossou; Esaï Gimatal Anagonou; Gilbert Adjimon Ayélo; Anita Carolle Akpéédjé Wadagni; Yves Thierry Barogui; Jean Gabin Houezo; Roch Christian Johnson (Public Library of Science (PLoS), 2022)
Introduction In the absence of early treatment, leprosy, a neglected tropical disease, due to Mycobacterium leprae or Hansen Bacillus, causes irreversible grade 2 disability (G2D) numerous factors related to the individual, the community and the health care system are believed to be responsible for its late detection and management. This study aims to investigate the factors associated with belated screening for leprosy in Benin. Methods This was a cross-sectional, descriptive, and analytical study conducted from January 1 to June 31, 2019, involving all patients and staff in leprosy treatment centers and public peripheral level health structures in Benin. The dependent variable of the study was the presence or not of G2D, reflecting late or early screening. We used a logistic regression model, at the 5% threshold, to find the factors associated with late leprosy screening. The fit of the final model was assessed with the Hosmer-Lemeshow test. Results A number of 254 leprosy patients were included with a mean age of 48.24 ± 18.37 years. There was a male dominance with a sex ratio of 1.23 (140/114). The proportion of cases with G2D was 58.27%. Associated factors with its belated screening in Benin were (OR; 95%CI; p) the fear of stigma related to leprosy (8.11; 3.3-19.94; <0.001), multiple visits to traditional healers (5.20; 2.73-9.89; <0.001) and multiple visits to hospital practitioners (3.82; 2.01-7.27; <0.001). The unawareness of leprosy by 82.69% of the health workers so as the permanent decrease in material and financial resources allocated to leprosy control were identified as factors in link with the health system that helps explain this late detection. Conclusion This study shows the need to implement strategies in the control programs to strengthen the diagnostic abilities of health workers, to improve the level of knowledge of the population on the early signs and symptoms of leprosy, to reduce stigmatization and to ban all forms of discrimination against leprosy patients.